Experimental models of orthodontic tooth movement and their effects on periodontal tissues remodelling - Nogueira, Andressa V.B. [UNESP]; Marcantonio, Camila C. [UNESP]; de Molon, Rafael S. [UNESP]; Leguizamón, Natalia D.P. [UNESP]; Silva, Renata C.L. [UNESP]; Deschner, James; Cerri, Paulo S. [UNESP]; Cirelli, Joni A. [UNESP] (Elsevier, 2021)
Objectives: The present study aimed to compare two different models of orthodontic tooth movement (OTM) in rats by evaluating tooth movement efficiency and periodontal tissues remodelling. Design: Fifteen animals were randomly distributed into 3 groups: control group (untreated); ligature appliance (LA) as experimental OTM using a closed coil spring fixed around maxillary first molar by steel ligature; occlusal appliance (OA) as experimental OTM using a closed coil spring attached on the occlusal surface of the maxillary first molar. After 15 days, all animals were euthanized, and the maxilla of each animal was collected for qPCR, micro-computed tomography, and histological analyses. Results: Interleukin-1 beta, interleukin-6, and tumor necrosis factor-alpha gene expressions were significantly upregulated in the animals of the LA group as compared to the other groups. No significant difference was observed in tooth displacement between both methods. The LA group presented higher linear bone loss and lower values of bone volume fraction, bone mineral density, trabecular number and increased values of trabecular separation compared to the other groups. The birefringent collagen content in the tension side of the periodontal ligament contained significantly lower collagen content in the LA group than in the control group. Furthermore, on the pressure side, the collagen content was significantly lower in the LA and OA groups than in the control group. Conclusions: The OA group presented little or no deleterious effect on periodontal tissues compared to the LA group, suggesting its use may be more reliable for OTM induction in rats for 15 days.
Keywords: Alveolar bone loss; Bone remodelling; Orthodontic tooth movement